Nitrous oxide emissions associated with nitrogen fixation by grain legumes - Zhong, Zhaozhan; Lemke, Reynald L.; Nelson, Louise M. (Soil biology & biochemistry, 2009)
Nitrous oxide (N 2O) emissions and biological nitrogen (N 2) fixation by grain legumes are two major processes of N transformation in agroecosystems. However, the relationship between these two processes is not well understood. The objective of this study was to quantify N 2O emissions associated with N 2 fixation by grain legumes under controlled conditions. The denitrifying capability of two Rhizobium leguminosarum biovar viciae strains, 99A1 and RGP2, was tested in pure culture in the presence of nitrate and in symbiosis with lentil ( Lens esculenta Moench) and pea ( Pisum sativum L.), respectively, in sterile Leonard jars. Lentil and pea, either inoculated or N-fertilized, were grown in soil boxes under controlled conditions. Profile N 2O concentration and surface N 2O emissions were measured from soil–crop systems, and were compared with that of a cereal – spring wheat ( Triticum aestivum L. ac. Barrie). Results indicated that: 1) neither R. leguminosarum strain, 99A1 or RGP2 was capable of denitrification in pure culture, nor in symbiosis with lentil and pea in sterile Leonard jars, suggesting that introducing these Rhizobium into soils through rhizobial inoculation onto lentil and pea will not increase denitrification or N 2O emissions; 2) soil-emitted N 2O from well-nodulated lentil and pea crops grown under controlled conditions was not significantly different than that from the check treatments, indicating that biological N 2 fixation by lentil and pea was not a direct source of N 2O emissions.